Tamsulosin versus tadalafil as medical expulsive therapy of distal ureteric stones: a comparative study - Parikh, Chirag; Gurjar, Vipul; Shah, Sneh (International Surgery Journal, 2019)
Background: The management of patients with ureteral calculi has changed dramatically in the current era, with the conservative approach being the primary focus, its main benefit being minimum patient morbidity. The use of the expectant approach for distal ureteric stones can be extended with the use of adjuvant medical expulsive therapy (MET), which is able to reduce symptoms and facilitate stone expulsion. The present study was thus conducted to determine single best monotherapy for medical expulsive therapy of distal ureteric stones by comparing Tadalaﬁl and Tamsulosin. Methods: A hospital based comparative study was conducted at Department of Surgery of a tertiary care hospital. A total of 60 eligible cases of lower uretric calculus were included in the study. These 60 patients were then divided into 2 groups of 30 each to receive one of the two medical therapy i.e. Tadalaﬁl and Tamsulosin. Results: Mean expulsion of calculi was significantly earlier in patients managed by tadalafil as compared to tamsulosin (13.1 vs 16.92 days; p<0.05). Complete expulsion was seen in 86.7% cases on tadalafil as compared to only 63.3% cases on tamsulosin (p<0.05). Mean analgesic use (2.69 vs 1.81; p<0.05) and episodes of colicy pain (1.41 vs 0.43; p<0.05) were significantly higher in patients managed by tamsulosin. The number of hospital visits required during treatment was also more with tamsulosin, but the difference did not reach significance levels (2.56 vs 2.02 days; p=0.06). No difference was seen in the adverse effect profile of both drugs. Conclusions: Tadalafil also provides early stone expulsion, a greater decrease in colicky pain episodes, and a greater decrease in analgesic requirement. Both drugs are safe, effective, and well tolerated with minor side effects. Thus tadalafil is safe, efficacious, and well tolerated as medical expulsive therapy for distal ureteric stones.